Approximation of some classes of periodic functions of many variables - Tovkach, R. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain the exact order of deviations of Fejér sums on the class of continuous functions. This order is determined by a given majorant of the best approximations.